Quranic Parenting: The Concept of Parenting in Islamic Perspective - Rubini Rubini; Cahya Edi Setyawan (Al-Misbah: Jurnal Islamic Studies, 2021)
The first and main children’s education is family education. In order to form children to be pious and faithful toward the One Almighty God, have noble characters that involve ethics, moral, and manners. This article aims to explain the foundation, principles and how it is performed and what methods utilized in the Quranic parenting. Those objectives are explained and framed in Islamic values. This article utilizes library research method. The data sources are taken from primary and secondary data. The primary data is Quranic Parenting: Success Tips to Educate Students based on the Al-Qur’an (Quranic Parenting: Tips for Success in Educating Children according to the Qur'an). Based on the result, the foundations of children’s parenting are Al Quran, Hadiths, and Ijma’ Ulama, the Act of National Education System (Sisdiknas) No.20 Year 2003 Article 7 Paragraph 2, and Act of the Republic of Indonesia No.23, Year 2002 article 26 paragraph 1. While the principles of parenting are to maintain the children’s nature (almuhafazoh), develop their potentials (at-tanmiyah), provide a clear guidance (at-taujid), gradually (at-tararruj). The parenting methods are Exemplary, Habituation, Attention, Rewards, and Punishments.